STUDYING OF SENSORS OPERATION STABILITY ENET WEBCAMERA AS A FUNCTION OF CAPTURED IMAGE STATISTICALPROPERTIES (MEAN &STANDARD DEVIATION) FOR DIFFERENTINTENSITIES BY FLORESCENT LIGHT. - Abbas, H.; Hussains, Z.; Abd Muslim, Sh.; Alzaki, A. (Iraqi Journal of Science, 2024)
The distortion, which occurs to the image often affects the existing amount ofinformation, weakens its sharpness and decreases its contrast and thus leads to overlapthe details of various regions and decrease image resolution. White test images are usedto determine the image quality and reveal the analysis ability of different visual systemswhere we depended in our study on white test images, studying distribution of the lightintensity of the image and figure out the relationship between the average and thestandard deviation to the picture to study the optical intensity function by using the testimage and the result to restrict the efficiency of the optical system. The technological results of contrast calculate are near to other different RGB colour band and gave moreprecise measurement in evaluating the quality as a function of the light intensity .